Ipsilateral Versus Contralateral Hamstring Grafts in Anterior Cruciate Ligament Reconstruction: A Prospective Randomized Trial. (November 2013) - McRae, Sheila; Leiter, Jeff; McCormack, Robert; Old, Jason; MacDonald, Peter
Background: Benefits of graft harvest from the side contralateral to the anterior cruciate ligament (ACL)–deficient leg have been identified when using bone–patellar tendon–bone autografts in ACL reconstruction (ACLR). As hamstring tendon autografts are becoming more commonly used, a study examining the effect of contralateral graft harvest of semitendinosus gracilis (STG) tendons on patient quality of life was conducted. Purpose: To evaluate if ACLR using a hamstring tendon autograft results in better patient quality of life if the graft is harvested from the leg contralateral to the ACL rupture compared with the ipsilateral leg. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A total of 100 participants between 16 and 50 years of age with a complete ACL tear were randomly assigned to undergo ACLR using either the ipsilateral or contralateral leg as the STG graft donor. Primary outcome measures were the ACL Quality of Life questionnaire (ACL-QOL), concentric knee flexion and extension strength at 60 and 240 deg/s, International Knee Documentation Committee (IKDC) knee assessment form, early postoperative pain and diary of analgesic use, and rate of reruptures. Outcome measures were evaluated before surgery and at 3, 6, 12, and 24 months after surgery. Results: The ACL-QOL score improved over time for both groups ( P < .001), and there were no significant differences between groups at any time point ( P = .528). Significant differences in knee flexion and extension strength were found at 3 months after surgery. There were no differences between groups in IKDC knee assessment scores or rerupture rates. Conclusion: There does not appear to be any measurable benefit or drawback in quality of life to the use of an STG graft from the unaffected limb. In light of this finding, further research to examine other possible effects on agility and balance as well as time and ability to return to sport should be conducted. Longer term follow-up beyond 2 years would allow for a more thorough evaluation of the risk of reruptures or contralateral reruptures using this novel approach.